PET (Polyethylene Terephthalate) composite resin material for packaging bottle as well as production process and application of PET composite resin material
A PET composite resin material is developed by modifying PET with a chain-extended polymer and multi-walled carbon nanotubes, and adding thermotropic liquid crystal polymers to address the limitations of PET in beer packaging, providing improved mechanical strength and gas barrier properties.
Patent Information
- Application Number
- CN202411763318.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional beer packaging materials, such as glass bottles, are fragile, heavy, and expensive, while plastic bottles lack sufficient gas barrier properties and pressure resistance for beer storage and transportation. PET materials have poor impact strength and gas barrier properties, making them unsuitable for beer packaging.
A PET composite resin material is produced by modifying PET with a chain-extended polymer and multi-walled carbon nanotubes using itaconic anhydride, and incorporating thermotropic liquid crystal polymers to enhance mechanical properties, gas barrier, and UV resistance.
The PET composite resin material exhibits strong mechanical properties, low gas permeability, and excellent UV resistance, suitable for beer packaging, replacing glass bottles.
Smart Images

Figure CN119220069A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of plastic packaging technology, and more specifically, to a PET composite resin material for packaging bottles and a production process and application thereof. Background Art
[0002] Traditional beer packaging bottles mainly include barrels, cans and glass bottles. Barreled beer is suitable for use in mass consumption places such as bars and restaurants, and is not easy to carry; cans are generally made of aluminum metal, which is expensive; glass bottles have mature manufacturing technology, high barrier properties to oxygen and carbon dioxide, which is conducive to the preservation and quality stability of beer, and high recycling rate, cheap and abundant manufacturing raw materials, so they are the most commonly used. However, glass bottles are fragile and heavy, which increases the transportation and storage costs of beer. In addition, glass bottles are brittle and relatively easy to explode. Therefore, it is necessary to seek high-quality and more economical materials for beer packaging.
[0003] Plastics are abundant in sources, cheap, low in density, easy to recycle, safer due to low brittleness, easy to carry, and convenient for transportation and storage. These advantages make them widely used in food, beverages, medicine, cosmetics, and agricultural chemicals. However, they are relatively rarely used in beer. This is because beer is different from general food, beverages, medicine, cosmetics, and other products. The pressure of beer after filling is high. In order to maintain quality and freshness, its packaging bottles must have high barrier properties to gases such as oxygen and carbon dioxide, and must be resistant to high pressure, certain temperatures, and UV rays.
[0004] Polyethylene terephthalate (PET) and other materials are milky white translucent or colorless transparent engineering plastics with strong resistance to friction and wear, strong creep resistance, good dimensional stability, high stiffness and hardness, but poor impact strength and heat resistance. In addition, although PET has certain barrier properties to gases such as oxygen and carbon dioxide, it is still not enough to meet the barrier requirements for beer filling and storage. Summary of the invention
[0005] In order to further meet the requirements of PET materials for beer canning and storage, the present application provides a PET composite resin material for packaging bottles and a production process and application.
[0006] In the first aspect, the present application provides a production process of a PET composite resin material for packaging bottles, which adopts the following technical solution:
[0007] A production process of a PET composite resin material for packaging bottles comprises the following steps: S1, preparing PET recycled particles; S2, preparing modified multi-walled carbon nanotubes; S3, preparing and molding: PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymers are mixed in proportion, and then placed in a twin-screw extruder, extruded into granules, and injection molded to obtain the PET composite resin material for packaging bottles; the PET recycled particles are prepared by preparing a chain extension polymer using allyl glycidyl ether, 3-methoxymethyl acrylate, and 2-vinylnaphthalene monomers, and the chain extension polymer is mixed with PET and melt-extruded; the modified multi-walled carbon nanotubes are prepared by acidifying the multi-walled carbon nanotubes and modifying them with itaconic anhydride.
[0008] By adopting the above technical scheme, PET is modified by chain extension polymer, multi-walled carbon nanotubes are modified by itaconic anhydride, and then thermotropic liquid crystal polymer is added to prepare a PET composite resin material for packaging bottles with strong mechanical properties, good gas barrier properties, low transmittance and excellent UV resistance.
[0009] Preferably, S1 specifically includes the following steps: S1.1, preparing a chain-extended polymer: under nitrogen, dissolving and mixing allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran in proportion, reacting at 70-80°C for 20-24h, then stopping the reaction, and then adding methanol to the reaction solution for precipitation, filtering, and vacuum drying to obtain a chain-extended copolymer; S1.2, mixing the chain-extended copolymer and PET, melt-extruding and granulating at 250-270°C to obtain PET recycled particles.
[0010] By adopting the above technical scheme, allyl glycidyl ether, 3-methoxymethyl acrylate, and 2-vinylnaphthalene are used as polymerization monomers, ammonium persulfate is used as an initiator, and 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid is used as a chain transfer agent to prepare a chain-extended copolymer with a high epoxy group content, thereby chain-extending PET, improving its branching degree, increasing its shear-thinning behavior, and improving its UV resistance through the naphthalene ring in the chain-extended copolymer.
[0011] Preferably, the amount ratio of allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran is: (5-9) g: (2-3) g: (1-1.5) g: (0.15-0.2) g: (0.8-1.2) g: (40-60) mL; the amount ratio of the chain extension copolymer and PET is: (2-7) g: (50-60) g; the melt index of the PET is 12.3-14.6 g / 10 min.
[0012] By adopting the above technical solution, the comprehensive performance of the PET recycled particles prepared at this ratio is the best.
[0013] Preferably, S2 specifically includes the following steps: S2.1, mixing the concentrated acid mixture with the multi-walled carbon nanotubes, ultrasonically dispersing them uniformly, then stirring and refluxing at 100-120°C for 2-3h, filtering, washing with deionized water until the filtrate is neutral, and vacuum drying to obtain acid-modified carbon nanotubes; S2.2, mixing the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid, and tetrahydrofuran, reacting at 55-65°C for 3-4h, filtering, washing with ethanol and water alternately until the filtrate is neutral, and vacuum drying to obtain secondary modified carbon nanotubes.
[0014] By adopting the above technical solution, multi-walled carbon nanotubes are acidified and then modified with itaconic anhydride to enhance their dispersibility in PET recycled particles, enhance the interfacial bonding force with thermotropic liquid crystal polymers, improve mechanical properties, and improve the gas barrier rate of oxygen and carbon dioxide. By adding thermotropic liquid crystal polymers, the overall viscosity is reduced, the fluidity is improved, and its processing performance is improved.
[0015] Preferably, the concentrated acid mixture includes concentrated nitric acid and concentrated sulfuric acid, and the mass ratio of concentrated nitric acid to concentrated sulfuric acid is (1-1.5): (2-4); the dosage ratio of the concentrated acid mixture to multi-walled carbon nanotubes is (2-3.5) mL: (2-4) g; the dosage ratio of the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid, and tetrahydrofuran is (3-5) g: (15-22) g: (10-12) mL: (100-200) mL.
[0016] By adopting the above technical scheme, a large number of hydroxyl and carboxyl groups are introduced into the multi-walled carbon nanotubes after acidification, and then itaconic anhydride is grafted to reduce its agglomeration, improve its dispersibility, increase the active sites, and improve its interface bonding strength with PET recycled particles and thermotropic liquid crystal polymers.
[0017] Preferably, the mass ratio of the PET recycled particles, the modified multi-walled carbon nanotubes and the thermotropic liquid crystal polymer is (35-50):(5.5-8.4):(4-6).
[0018] By adopting the above technical solution, the prepared PET composite resin material for packaging bottles has the best comprehensive performance.
[0019] Preferably, the melt temperature during the extrusion granulation is 260-270°C, the head temperature is 250-260°C, the residence time is 3-5min, the pressure is 6-10MPa, and the screw speed is 180-220rpm; the nozzle temperature during the injection molding is 240-260°C, the first stage temperature is 240-260°C, the second stage temperature is 260-270°C, and the injection pressure is 50-80MPa.
[0020] In a second aspect, the present application provides a PET composite resin material for packaging bottles, which is prepared by the above production process.
[0021] In a third aspect, the present application provides an application of a PET composite resin material for packaging bottles, wherein the PET composite resin material for packaging bottles is used for beer packaging bottles.
[0022] In summary, this application has the following beneficial effects:
[0023] 1. This application adopts chain-extended polymer to modify PET, uses itaconic anhydride to modify multi-walled carbon nanotubes, and then adds thermotropic liquid crystal polymers to prepare a PET composite resin material for packaging bottles with strong mechanical properties, good gas barrier properties, low transmittance, and excellent UV resistance.
[0024] 2. In the present application, allyl glycidyl ether, 3-methoxymethyl acrylate and 2-vinylnaphthalene are preferably used as polymerization monomers, ammonium persulfate is used as initiator and 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid is used as chain transfer agent to prepare a chain-extended copolymer with a high epoxy content, thereby chain-extending PET, improving its branching degree and shear-thinning behavior, and improving its UV resistance through the naphthalene ring in the chain-extended copolymer.
[0025] 2. In this application, multi-walled carbon nanotubes are acidified and then modified with itaconic anhydride to enhance their dispersibility in PET recycled particles, enhance the interfacial bonding force with thermotropic liquid crystal polymers, improve mechanical properties, and improve the gas barrier rate of oxygen and carbon dioxide. Thermotropic liquid crystal polymers are added to reduce the overall viscosity, improve fluidity, and improve its processing performance.
[0026] 3. The PET composite resin material for packaging bottles produced by the production process of the present application has the characteristics of strong impact resistance, resistance to cold and heat, high tensile strength, low oxygen and carbon dioxide permeability, and excellent anti-ultraviolet performance, and is expected to replace glass bottles for beer packaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : Hydrogen spectrum of the chain-extended polymer prepared in Example 1 of the present application, wherein the structure of R1 is 2-[dodecylthio(thiocarbonyl)thio]-, and the structure of R2 is (2-methylpropionic acid)-.
[0028] Figure 2 : Infrared spectrum of the modified multi-walled carbon nanotubes prepared in Example 1 of the present application, wherein a is a multi-walled carbon nanotube, b is an acidified multi-walled carbon nanotube, and c is a modified multi-walled carbon nanotube.
[0029] Figure 3: Cross-sectional SEM images of the PET composite resin material for packaging bottles of the present application, wherein (a) is Comparative Example 2, (b) is Comparative Example 3. (c) and (d) are Example 1, and PET particles in (d) refer to PET recycled particles, TLCP refers to thermotropic liquid crystal polymer, and CNTs refers to modified multi-walled carbon nanotubes. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the embodiments.
[0031] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0032] Example 1
[0033] A PET composite resin material for packaging bottles is prepared by the following steps:
[0034] S1, preparation of PET recycled particles:
[0035] S1.1, preparing a chain-extended polymer: under nitrogen, allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran are dissolved and mixed in proportion, reacted at 70°C for 24 hours, and then the reaction is stopped. Then, methanol is added to the reaction solution for precipitation, filtered, and vacuum dried to obtain a chain-extended copolymer; the amount ratio of allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran is: 5g:2g:1g:0.15g:0.8g:40mL;
[0036] S1.2, mixing the chain extension copolymer and PET, melt-extruding and granulating at 250° C. to obtain PET recycled particles; the amount ratio of the chain extension copolymer and PET is: 2g:50g.
[0037] The melt index of the obtained PET was 12.3 g / 10 min.
[0038] The melt index of the obtained PET recycled particles was 14.8 g / 10 min.
[0039] The average number of epoxy groups per molecule of the obtained chain-extended copolymer was 55.
[0040] S2, preparation of modified multi-walled carbon nanotubes:
[0041] S2.1, mixing the concentrated acid mixture with the multi-walled carbon nanotubes, uniformly dispersing by ultrasonication, then stirring and refluxing at 100°C for 3h, filtering, washing with deionized water until the filtrate is neutral, and vacuum drying to obtain acid-modified carbon nanotubes; the concentrated acid mixture comprises concentrated nitric acid and concentrated sulfuric acid, the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 1:2; the amount ratio of the concentrated acid mixture to the multi-walled carbon nanotubes is 2mL:2g;
[0042] S2.2, mixing the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid and tetrahydrofuran, reacting at 55°C for 4h, filtering, washing with ethanol and water alternately until the filtrate is neutral, and vacuum drying to obtain secondary modified carbon nanotubes; the amount ratio of the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid and tetrahydrofuran is 3g:15g:10mL:100mL;
[0043] S3, preparation and molding: PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymer are mixed in proportion, and then placed in a twin-screw extruder, extruded into granules, and injection molded to obtain PET composite resin material for packaging bottles; the mass ratio of the PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymer is 35:5.5:4; the melt temperature during the extrusion granulation is 260°C, the head temperature is 250°C, the residence time is 5min, the pressure is 6MPa, and the screw speed is 180rpm; the nozzle temperature during the injection molding is 240°C, the first stage temperature is 240°C, the second stage temperature is 260°C, and the injection pressure is 50MPa.
[0044] The thermotropic liquid crystal polymer (model VECTRA A950) was purchased from Celanese Corporation.
[0045] Using deuterated chloroform as solvent, the obtained chain-extended polymer was tested by hydrogen spectrum using a nuclear magnetic resonance spectrometer. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the proton hydrogen of the naphthalene ring of 2-vinylnaphthalene is in the 7.92-7.48 ppm region, the two methoxy groups of 3-methoxy methyl acrylate are in the 3.71 ppm and 3.42 ppm regions respectively, and the chemical shifts of the methylene oxygen of allyl glycidyl ether are 3.6-3.17 and 2.74-2.35 ppm. These results indicate that the chain-extended polymer has been successfully synthesized.
[0046] The infrared spectroscopy analysis and comparison of the multi-walled carbon nanotubes, acidified multi-walled carbon nanotubes and modified multi-walled carbon nanotubes in this embodiment are shown in the following figure. Figure 2 As shown. Figure 2 It can be seen that compared with multi-walled carbon nanotubes, acidified multi-walled carbon nanotubes have -1 and 1720cm -1Strong absorption peaks appeared. These two peaks are hydroxyl absorption peak and carbonyl absorption peak, indicating that the surface of acidified multi-walled carbon nanotubes has hydroxyl and carboxyl functional groups. After modification with itaconic anhydride, the modified multi-walled carbon nanotubes have a peak at 1730 cm -1 There appeared an absorption peak stronger than that of the acidified multi-walled carbon nanotubes, which indicated that the carboxyl groups of itaconic anhydride reacted with the hydroxyl groups of the acidified multi-walled carbon nanotubes to generate more carbonyl groups, indicating that the multi-walled carbon nanotubes were successfully modified.
[0047] Example 2
[0048] A PET composite resin material for packaging bottles is prepared by the following steps:
[0049] S1, preparation of PET recycled particles:
[0050] S1.1, preparation of chain extension polymer: under nitrogen, allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran are dissolved and mixed in proportion, reacted at 75°C for 22 hours, then the reaction is stopped, and then methanol is added to the reaction solution for precipitation, filtered, and vacuum dried to obtain a chain extension copolymer; the amount ratio of allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran is: 7g:2.5g:1.3g:0.18g:1g:50mL;
[0051] S1.2, mixing the chain extension copolymer and PET, melt-extrude and granulate at 260° C. to obtain PET recycled particles; the amount ratio of the chain extension copolymer and PET is 5 g:44 g.
[0052] The melt index of the obtained PET was 13.5 g / 10 min.
[0053] The melt index of the obtained PET recycled particles was 15.6 g / 10 min.
[0054] The average number of epoxy groups per molecule of the obtained chain-extended copolymer was 69.
[0055] S2, preparation of modified multi-walled carbon nanotubes:
[0056] S2.1, mixing the concentrated acid mixture with the multi-walled carbon nanotubes, uniformly dispersing them by ultrasonication, then stirring and refluxing at 110° C. for 2.5 h, filtering, washing with deionized water until the filtrate is neutral, and vacuum drying to obtain acid-modified carbon nanotubes; the concentrated acid mixture comprises concentrated nitric acid and concentrated sulfuric acid, and the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 1.3:3; the amount ratio of the concentrated acid mixture to the multi-walled carbon nanotubes is 2.8 mL:3 g;
[0057] S2.2, mixing the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid and tetrahydrofuran, reacting at 60°C for 3.5h, filtering, washing with ethanol and water alternately until the filtrate is neutral, and vacuum drying to obtain secondary modified carbon nanotubes; the amount ratio of the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid and tetrahydrofuran is 4g:18g:11mL:150mL;
[0058] S3, preparation and molding: PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymer are mixed in proportion, and then placed in a twin-screw extruder, extruded into granules, and injection molded to obtain PET composite resin material for packaging bottles; the mass ratio of the PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymer is 45:6.5:5; the melt temperature during the extrusion granulation is 265°C, the head temperature is 255°C, the residence time is 4min, the pressure is 8MPa, and the screw speed is 200rpm; the nozzle temperature during the injection molding is 250°C, the first stage temperature is 250°C, the second stage temperature is 265°C, and the injection pressure is 65MPa.
[0059] The thermotropic liquid crystal polymer (model VECTRA A950) was purchased from Celanese Corporation.
[0060] Example 3
[0061] A PET composite resin material for packaging bottles is prepared by the following steps:
[0062] S1, preparation of PET recycled particles:
[0063] S1.1, preparation of chain extension polymer: under nitrogen, allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran are dissolved and mixed in proportion, reacted at 80°C for 20 hours, then the reaction is stopped, and then methanol is added to the reaction solution for precipitation, filtered, and vacuum dried to obtain a chain extension copolymer; the amount ratio of allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran is: 9g:3g:1.5g:0.2g:1.2g:60mL;
[0064] S1.2, mixing the chain extension copolymer and PET, melt-extruding and granulating at 270° C. to obtain PET recycled particles; the amount ratio of the chain extension copolymer and PET is: 7g:60g.
[0065] The melt index of the obtained PET was 14.6 g / 10 min.
[0066] The melt index of the obtained PET recycled particles was 16.4 g / 10 min.
[0067] The average number of epoxy groups per molecule of the obtained chain-extended copolymer was 82.
[0068] S2, preparation of modified multi-walled carbon nanotubes:
[0069] S2.1, mixing the concentrated acid mixture with the multi-walled carbon nanotubes, uniformly dispersing them by ultrasonication, then stirring and refluxing at 120° C. for 2 h, filtering, washing with deionized water until the filtrate is neutral, and vacuum drying to obtain acid-modified carbon nanotubes; the concentrated acid mixture comprises concentrated nitric acid and concentrated sulfuric acid, and the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 1.5:4; the amount ratio of the concentrated acid mixture to the multi-walled carbon nanotubes is 3.5 mL:4 g;
[0070] S2.2, mixing the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid and tetrahydrofuran, reacting at 65°C for 3h, filtering, washing with ethanol and water alternately until the filtrate is neutral, and vacuum drying to obtain secondary modified carbon nanotubes; the amount ratio of the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid and tetrahydrofuran is 5g:22g:12mL:200mL;
[0071] S3, preparation and molding: PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymer are mixed in proportion, and then placed in a twin-screw extruder, extruded into granules, and injection molded to obtain a PET composite resin material for packaging bottles; the mass ratio of the PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymer is 50:8.4:6; the melt temperature during the extrusion granulation is 270°C, the head temperature is 260°C, the residence time is 3min, the pressure is 10MPa, and the screw speed is 220rpm; the nozzle temperature during the injection molding is 260°C, the first stage temperature is 260°C, the second stage temperature is 270°C, and the injection pressure is 80MPa.
[0072] The thermotropic liquid crystal polymer (model VECTRA A950) was purchased from Celanese Corporation.
[0073] Comparative Example 1
[0074] The method is the same as Example 1, except that the chain extender ADR4400 (purchased from Shanghai Nanosu Alloy Technology Co., Ltd.) is used instead of the chain extended copolymer to prepare the PET recycled particles.
[0075] Comparative Example 2
[0076] The same as Example 1, except that multi-walled carbon nanotubes are used instead of modified multi-walled carbon nanotubes.
[0077] Comparative Example 3
[0078] The same as Example 1, except that PET is directly used instead of PET recycled particles.
[0079] Comparative Example 4
[0080] The same as Example 1, except that no thermotropic liquid crystal polymer is added.
[0081] Performance testing
[0082] After the PET composite resin material for packaging bottles prepared in Example 1, Comparative Example 2 and Comparative Example 3 was quenched, its cross-sectional morphology was observed using a scanning electron microscope. Figure 3 shown.
[0083] from Figure 3 As can be seen from (a) in the figure, the cross-sectional surface of the PET composite resin material for packaging bottles prepared in Comparative Example 2 is relatively rough, with many stone-like protrusions and concave pits existing in the matrix. This is because the unmodified multi-walled carbon nanotubes have poor compatibility with the thermotropic liquid crystal polymer and the PET recycled particles. Figure 3 As can be seen from (b) in the figure, the size and number of the stone-like protrusions and concave pits on the cross-sectional surface of the PET composite resin material for packaging bottles prepared in Comparative Example 3 are relatively small, indicating that the modified multi-walled carbon nanotubes can improve the compatibility of thermotropic liquid crystal polymers and PET to a certain extent; Figure 3 It can be seen from (c) that the size and number of stone-like protrusions and concave pits of the PET composite resin material for packaging bottles prepared in Example 1 are the smallest, indicating that the modified multi-walled carbon nanotubes, liquid crystal polymers and PET recycled particles have the best compatibility; Figure 3 As can be seen in (d), the modified multi-walled carbon nanotubes are preferentially positioned on the PET recycled particles, increasing the interfacial bonding between the PET recycled particles and the liquid crystal polymer.
[0084] (1) According to the test method of GB / T1843-2008, the PET composite resin materials for packaging bottles prepared in various embodiments and comparative examples were subjected to a room temperature notched impact strength test.
[0085] (2) According to the test method of GB / T1038.1-2022, the oxygen and carbon dioxide transmission rates of the PET composite resin materials for packaging bottles prepared in each embodiment and comparative example were tested.
[0086] (3) According to the test method of GBT1040.2-2022, the tensile strength of the PET composite resin material for packaging bottles prepared in each embodiment and comparative example was tested.
[0087] (4) The ultraviolet transmittance of the PET composite resin material for packaging bottles prepared in each embodiment and comparative example in the long-wave (UVA) and medium-wave (UVB) bands was measured using a spectrometer, and the full-band ultraviolet transmittance was calculated.
[0088] The results are shown in Table 1.
[0089] Table 1. Performance test results
[0090] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Notched impact strength at room temperature (KJ / m 2 )]]> 10.5 10.8 9.9 6.7 4.4 5.5 7.8 <![CDATA[Wet heat notched impact strength (KJ / m 2 )]]> 8.3 8.6 7.5 4.2 2.6 3.8 3.9 <![CDATA[Wet and cold notched impact strength (KJ / m 2 )]]> 7.5 7.7 6.3 2.2 2.3 3.5 4.8 Tensile strength (MPa) 71.2 70.5 69.2 42.3 25.6 31.4 58.1 <![CDATA[Oxygen transmission rate cm 3 / (m 2 ·24 h·0.1 MPa) (25 °C, 0% humidity)]]> 4.5 5.2 5.8 78.5 46.3 93.2 32.1 <![CDATA[Carbon dioxide transmission rate cm 3 / (m 2 ·24h·0.1MPa) (25 °C, 85% humidity)]]> 12.6 14.3 13.8 83.1 55.7 102.6 41.3 UVA transmittance (%) 3.6 4.7 4.2 77.5 16.8 78.3 28.4 UVB transmittance (%) 1.3 2.1 1.5 62.3 14.1 63.9 27.2
[0091] As can be seen from Table 1, the PET composite resin materials for packaging bottles prepared in Examples 1 to 3 of the present application have strong impact resistance, resistance to cold and heat, high tensile strength, low oxygen and carbon dioxide permeability, and excellent anti-ultraviolet performance.
[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.
Claims
1. A production process of PET composite resin material for packaging bottles, characterized in that: The following steps are involved: S1, preparing PET recycled particles; S2, preparing modified multi-walled carbon nanotubes; S3, preparing molding: PET recycled particles, modified multi-walled carbon nanotubes, and thermotropic liquid crystal polymers are mixed in proportion, and then placed in a twin-screw extruder, extruded into granules, and injection molded to obtain PET composite resin materials for packaging bottles; the PET recycled particles are prepared by preparing chain extension polymers using allyl glycidyl ether, 3-methoxymethyl acrylate, and 2-vinylnaphthalene monomers, and the chain extension polymer is mixed with PET and melt-extruded in two steps; the modified multi-walled carbon nanotubes are prepared by acidifying multi-walled carbon nanotubes and modifying them with itaconic anhydride in two steps.
2. The production process of a PET composite resin material for packaging bottles according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1, preparing a chain-extended polymer: under nitrogen, allyl glycidyl ether, methyl 3-methoxyacrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran are dissolved and mixed in proportion, reacted at 70-80°C for 20-24h, and then the reaction is stopped. Then, methanol is added to the reaction solution for precipitation, filtered, and vacuum dried to obtain a chain-extended copolymer; S1.2, the chain-extended copolymer and PET are mixed, melt-extruded and granulated at 250-270°C to obtain PET recycled particles.
3. The production process of a PET composite resin material for packaging bottles according to claim 2, characterized in that: The dosage ratio of allyl glycidyl ether, 3-methoxymethyl acrylate, 2-vinylnaphthalene, ammonium persulfate, 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid and tetrahydrofuran is: (5-9) g: (2-3) g: (1-1.5) g: (0.15-0.2) g: (0.8-1.2) g: (40-60) mL; the dosage ratio of the chain extension copolymer and PET is: (2-7) g: (50-60) g.
4. The production process of a PET composite resin material for packaging bottles according to claim 3, characterized in that: The S2 specifically includes the following steps: S2.1, mixing the concentrated acid mixture with the multi-walled carbon nanotubes, ultrasonically dispersing them uniformly, then stirring and refluxing at 100-120°C for 2-3h, filtering, washing with deionized water until the filtrate is neutral, and vacuum drying to obtain acid-modified carbon nanotubes; S2.2, mixing the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid, and tetrahydrofuran, reacting at 55-65°C for 3-4h, filtering, washing with ethanol and water alternately until the filtrate is neutral, and vacuum drying to obtain secondary modified carbon nanotubes.
5. The production process of a PET composite resin material for packaging bottles according to claim 4, characterized in that: The concentrated acid mixture includes concentrated nitric acid and concentrated sulfuric acid, and the mass ratio of concentrated nitric acid to concentrated sulfuric acid is (1-1.5): (2-4); the dosage ratio of the concentrated acid mixture to multi-walled carbon nanotubes is (2-3.5) mL: (2-4) g; the dosage ratio of the acidified carbon nanotubes, itaconic anhydride, hydrochloric acid, and tetrahydrofuran is (3-5) g: (15-22) g: (10-12) mL: (100-200) mL.
6. The production process of a PET composite resin material for packaging bottles according to claim 5, characterized in that: The mass ratio of the PET recycled particles, the modified multi-walled carbon nanotubes and the thermotropic liquid crystal polymer is (35-50): (5.5-8.4): (4-6).
7. The production process of a PET composite resin material for packaging bottles according to claim 6, characterized in that: The melt index of the PET is 12.3-14.6 g / 10 min.
8. The production process of a PET composite resin material for packaging bottles according to claim 7, characterized in that: The melt temperature during extrusion granulation is 260-270°C, the head temperature is 250-260°C, the residence time is 3-5min, the pressure is 6-10MPa, and the screw speed is 180-220rpm; the nozzle temperature during injection molding is 240-260°C, the first stage temperature is 240-260°C, the second stage temperature is 260-270°C, and the injection pressure is 50-80MPa.
9. A PET composite resin material for packaging bottles, characterized in that: The method is prepared by the production process of the PET composite resin material for packaging bottles according to any one of claims 1 to 8.
10. The PET composite resin material for packaging bottles according to claim 9, characterized in that: Used to prepare beer packaging bottles.
